Recipes for love and murder. Series one [videorecording (DVD)] - Jeynes, Karen; Kennedy, Maria Doyle; Kgoroge, Tony; Fisher, Kylie; Steyn, Jennifer; Greeff, Arno; Landrew, Elton, 1975-; Van der Walt, Daneel; Fourie, Bennie; Heeger, Khadija; Committie, Alan; Andrew, Sally (Acorn, 2022)
Kind, quiet Tannie Maria isn't a woman who draws much notice. She leads a solitary life, writing recipes for the local gazette, cooking with ingredients from her garden, and chatting with her pet chicken, Morag. When Maria becomes the newspaper's advice columnist, she peppers her responses with delectable recipes to help people fix their problems. But after a woman who wrote to her turns up dead, Maria and her colleague, rookie journalist Jessie, spring into action. They're determined to solve the murder in their small South African town, to the annoyance of a police detective.